2021
DOI: 10.1016/j.toxrep.2021.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Chloroquine ameliorates bone loss induced by d-galactose in male rats via inhibition of ERK associated osteoclastogenesis and antioxidant effect

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 56 publications
3
4
0
Order By: Relevance
“…Our in vitro study demonstrated that D-gal and hyperinsulinism promoted osteoclast differentiation equally. Consistent with this finding an increased secretory activity of the osteoclasts has been well-established at either 8 weeks after the onset of D-gal injection- or long-term HFD consumption-induced osteoporosis, as indicated by an elevation of cathepsin K level in serum 41 , 53 55 . These previous findings suggested that either D-gal- or hyperinsulinism-induced increase in osteoclast number was mediated by the increased secretory activity of osteoclasts, resulting in increased osteoclast differentiation.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Our in vitro study demonstrated that D-gal and hyperinsulinism promoted osteoclast differentiation equally. Consistent with this finding an increased secretory activity of the osteoclasts has been well-established at either 8 weeks after the onset of D-gal injection- or long-term HFD consumption-induced osteoporosis, as indicated by an elevation of cathepsin K level in serum 41 , 53 55 . These previous findings suggested that either D-gal- or hyperinsulinism-induced increase in osteoclast number was mediated by the increased secretory activity of osteoclasts, resulting in increased osteoclast differentiation.…”
Section: Discussionsupporting
confidence: 72%
“…At week 8, D-gal plus HFD-induced aging and obesity both independently and synergistically stimulated the increases in serum CTX-I level and RANKL mRNA expression in the bone. Interestingly, the role of oxidative stress in the alteration of RANKL expression has been well-established in aging models 40 , 41 . Specifically, a prior study in rats revealed that 8 weeks of D-gal administration compromised the activity of antioxidant enzymes (superoxide dismutase and catalase) in serum, increased serum RANKL level, and increased osteoporosis 41 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Age‐related bone loss induced by d ‐galactose through the activation of RAS locally in skeletal tissues plays a pivotal role in bone remodeling and metabolism [23, 24]. In the current study, treatment with d ‐galactose dramatically augmented the expression of AT 1 R in bone over AT 2 R, which was consistent with a former study conducted by [5] in d ‐galactose‐induced aging in rats.…”
Section: Discussionsupporting
confidence: 91%
“…Data were statistically evaluated using one-way ANOVA followed by Tukey's multiple comparisons test. Differences were considered statistically significant when *P < 0.05 compared with the control group and @ P < 0.05 compared with Dgal-treated group pivotal role in bone remodeling and metabolism [23,24].…”
Section: Discussionmentioning
confidence: 99%